Effect of establishment methods and varieties on yield and economics of linseed in vertisols: EFFECT OF ESTABLISHMENT METHODS AND VARIETIES ON YIELD AND ECONOMICS OF LINSEED - SANJAY K DWIVEDI; D CHANDRAKAR; P K SINGH (Journal of Oilseeds Research, 2018)
The field experiment on the effect of establishment methods and varieties on yield components, yield and economics of linseed was undertaken in Vertisols during rabi season of 2013-14 and 2014-15. The experiment was laid out in split plot design with allocation of methods of establishment in main plot and varieties in sub plot. The treatments were replicated four times. The treatments comprised of three methods of establishment i.e. M1: Dry seeding with planking followed by irrigation, M2: Dry seeding without planking followed by irrigation and M3: Seeding after pre-sowing irrigation and four varieties i.e. V1: T 397 (National check), V2: RLC 92, V3: Indira Alsi 32 and V4: Shekhar. Linseed sowing by dry seeding with planking followed by irrigation (M1) gave higher plant population, enhanced the growth and yield attributes which in turn resulted in significantly higher seed yield (1298 kg/ha) as well as net income (`37938/ha) amongst methods of establishment. With respect to varieties, RLC-92 (V2) showed good crop stand establishment, highest oil content (41.4%) and produced vigorous growth and superior yield attributes and highest seed yield (1293 kg/ha) of linseed as well as accrued handsome net profits (`37872/ha) and B:C ratio (1.91). The interaction effect among the methods of establishment and varieties was found non-significant in terms of yield and important yield attributing characters.